FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN TERHADAP PRODUK IKAN KALENG MEREK PANTAI MANADO PT. SINAR PURE FOODS INTERNATIONAL BITUNG - Tungkele, Rini; Roring, Mieke; Sumampouw, Harry (JURNAL ADMINISTRASI BISNIS (JAB), 2015)
ABSTRACT : The development of the business world that is never separated from the competition, companies are required to always be creative and innovate in order to survive. In developing a product, the manufacturer must determine the quality, so as to position the product in the market. Quality is expected to offer superior products Competitor.With the product remains always had a fascination for consumers. Among the products with revenues, not in spite of the marketing system. This marketing system is a technique or way of sales to achieve results. marketing require good management so that the business could be better. improve product quality to meet the needs of consumers so as to maintain the achievements, as was done by Brand Canned Fish factory Manado Beach PT Sinar Pure Foods International Bitung consumers to feel attracted and buy products Canned Fish Brand Manado Beach at low prices and good product quality. This proves that the canned fish factory engaged in the effort to meet the expectations and needs of its customers, the strategy pursued is to lower prices, better quality products and brands that Good. increase product quality to meet the needs of consumers so able to maintain the success obtained, as was done by Brand Canned Fish factory Manado Beach PT Sinar Pure Foods International Bitung. Based on the description of the background issues that have been mentioned above, researchers interested in conducting research on consumer buying interest with title''faktors that affects consumer buying interest towards the product "brand canned fish beach manado" PT Sinar Pure Foods International Bitung.Keywords: Interests Buy Consumer, Products